Patentability of Patent Evergreening in the Pharmaceutical Sector: Novartis AG versus The Union of India - Hendrix, Tommy; Wijaya Holman, Angga (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2024)
This paper discusses the inventions in the pharmaceutical sector containing the nature of 'evergreening' based on the Supreme Court of India's ruling in Novartis's versus the Union of India. Patent ‘evergreening refers to the business practice of patent applications for inventions in the pharmaceuticals or medicines sector that are insignificant novel compared to previous similar inventions to extend the patent protection period that implies the increasing selling price of drugs on the market. These differences resulted in India's having to anticipate the legal issues and exclude patents for inventions containing 'evergreening' properties by applying high patentability requirements. Patent' evergreening' has implications for blocking the purpose of patent existence as a tool of dissemination of science because this practice extends the period of temporary monopoly rights ownership of patents and hinders public access to medicines at affordable prices. This research uses comparative legal methods to determine the characteristics of the patentability requirement between the Indian Patent Law, TRIPs, and the Indonesian Patent Law. The decision has implications for Indonesia as a consideration, especially for the Government of Indonesia in drafting the new law that anticipates the practice of patent 'evergreening' in Indonesia.